(3QSGdI NeGQ Hf LjT GdSdjeGfi GdYcGhis ((3GdCejQ YjSi GdJfhNi s)
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf Ld PcQg hHg CSJYjf ai LejY GdCehQ ef YHO CejQ GdeDefjf Ld PcQg ehdGfG SHMGfg heedhcg gGOi GdeSJLjHjf s
(3BNQgG (B:s
(3Ke fHJOF Hef gh eKdc afbJdge bJd GdcdGH hCbhGekG BNQjf ai GdYPGH hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds